Influences of an arrow`s aerodynamic pressure center on recurve bow shooting - Shen, W.; Hu, L.; Hu, J.; Xu, Y.; Xu, X.; Zheng, J. (Applied Sciences, 2025)
An arrow`s attack angle continuously changes during its flight, which affects the position of the aerodynamic pressure center. To account for the offset between the aerodynamic pressure center and the center of mass of an arrow in recurve bow shooting, two equations for describing the variation of the aerodynamic pressure center with the attack angles were fitted via CFD simulation. On this basis, a new theoretical aerodynamic model was developed by integrating the above equations with the current model to predict the flight along the outer ballistic trajectory more accurately than ever. With regard to actual archery competition occasions, the distance, initial velocity, and attack angle were set to 70 m, 57 m/s, and -3° to 3°, respectively; the attitude and trajectory of the arrow flying details under background wind, such as crosswind, headwind, and tailwind, were numerically analyzed to reveal the accuracy deviation mechanism. A comparison was conducted with previous models, indicating that the model proposed in this study achieved improvements in accuracy of 15% under crosswind conditions and 8% under headwind/tailwind conditions. The results could, from a fluid physics perspective, provide valuable recommendations not only for archers and coaches but also for arrow manufacturers.